2016
DOI: 10.1007/s00198-016-3678-4
|View full text |Cite
|
Sign up to set email alerts
|

Wheelchair use and lipophilic statin medications may influence bone loss in chronic spinal cord injury: findings from the FRASCI-bone loss study

Abstract: Purpose Spinal cord injury (SCI) increases the risk of osteoporosis and low-impact fractures, particularly at the knee. However, during the chronic phase of SCI, the natural history and factors associated with longitudinal change in bone density remain poorly characterized. In this study we prospectively assessed factors associated with change in bone density over a mean of 21 months in 152 men and women with chronic SCI. Methods A mixed model procedure with repeated measures was used to assess predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…All participants used a wheelchair as their primary mode of mobility; 75% had a motor‐complete injury. The mean BMI was 25.3 ± 5.0 kg/m; 55% of participants had normal vitamin D levels (>30 ng/mL). Nine participants were found to have a vitamin D deficiency (<30 ng/mL) and were treated with supplemental vitamin D prior to progressing in the study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All participants used a wheelchair as their primary mode of mobility; 75% had a motor‐complete injury. The mean BMI was 25.3 ± 5.0 kg/m; 55% of participants had normal vitamin D levels (>30 ng/mL). Nine participants were found to have a vitamin D deficiency (<30 ng/mL) and were treated with supplemental vitamin D prior to progressing in the study.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis following spinal cord injury (SCI) is thought to be based primarily on the loss of mechanical loading that occurs after lower extremity paralysis . Bone loss leads to fractures in up to 50% of individuals with SCI, with the majority of fractures occurring at the metaphyses of the proximal tibia and distal femur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it did not improve bone mineral density [ 72 , 73 ]. A recent prospective study of factors associated with a change in bone density in chronic SCI [ 74 ], also included participants with a mean age of 55.1 ± 14.4 (SD) years (ranging from 24.7–87.1 years). Interestingly, this large study with 152 participants, found that wheelchair users lost more bone mineral density at the knee than walkers per year, an effect that was independent of age.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of osteoporosis after SCI is multifactorial resulting from hormonal changes, neuronal mechanisms, autonomic denervation below injury level, and to a great extent from disuse . The loss of muscle contractions and weight‐bearing results in a lack of mechanical loading and subsequent bone loss.…”
Section: Introductionmentioning
confidence: 99%